Production of selenium nanoparticles in Pseudomonas putida KT2440 - Avendaño Vega, Roberto (2016)
Selenium (Se) is an essential element for the cell that has multiple applications in medicine and technology; microorganisms play an important role in Se transformations in the environment. Here we report the previously unidentified ability of the soil bacterium Pseudomonas putida KT2440 to synthesize nanoparticles of elemental selenium (nano-Se) from selenite. Our results show that P. putida is able to reduce selenite aerobically, but not selenate, to nano-Se. Kinetic analysis indicates that, in LB medium supplemented with selenite (1 mM), reduction to nano-Se occurs at a rate of 0.444 mmol L−1 h−1 beginning in the middle-exponential phase and with a final conversion yield of 89%. Measurements with a transmission electron microscope (TEM) show that nano-Se particles synthesized by P. putida have a size range of 100 to 500 nm and that they are located in the surrounding medium or bound to the cell membrane. Experiments involving dynamic light scattering (DLS) show that, in aqueous solution, recovered nano-Se particles have a size range of 70 to 360 nm. The rapid kinetics of conversion, easy retrieval of nano-Se and the metabolic versatility of P. putida offer the opportunity to use this model organism as a microbial factory for production of selenium nanoparticles.